Towards a unified taxonomic catalogue for the Chilean cacti: assembling molecular systematics and classical taxonomy - Walter, Helmut E.; Guerrero, Pablo C. (Phytotaxa, 2022)
The competition between floristic catalogues and the nomenclatural issues of the treated taxa, is a problem for the botanical knowledge of countries. Consequently, it seems to be necessary to merge former taxonomical proposals into a unified list based on phylogenetic hypotheses, the rules of nomenclature and dichotomous keys to the Chilean subfamilies, tribes and genera. With this approach we here propose an updated catalogue of the Chilean cacti. It would be necessary to merge the various taxonomic proposals into a unified list based on both phylogenetic hypotheses and the rules of nomenclature. With this approach, we here propose to updated the catalogue of Chilean cactus. A neotype was designated for Echinocactus jussieui. In addition, we present a dichotomous taxonomic key to the Chilean subfamilies, tribes, and genera.